Deconstructing Memory Johannes Cochlaeus's "Life of Martin Luther" between Polemics and "Invectivity" - Dietl, Cora (Journal of Early Modern Christianity, 2023)
Johannes Cochlaeus's Commentaria or Historia de actis et scriptis Martini Lutheri has been described as a "polemical invective." This essay discusses the double title and the double characterization of the work and argues that its aim is to deconstruct Luther's memory. Its effectivity derives from the combination of a polemical commentary and an invective biography. According to the Commentaria Luther's works disgrace the author, and according to the Historia the author disqualifies his own works.